ENZYMATIC COLOUR REMOVAL OF PULP AND PAPER MILL EFFLUENT BY DIFFERENT FUNGAL STRAINS - PRATIBHA SINGH,; ASHIMA SRIVASTAVA, (International Journal of Pharma and Bio Sciences, 2014)
Pulp and paper mill effluent is posing a serious threat to the water and soil components of the environment due to its brown colour and high level of toxicity. Fungal treatment is one of the efficient methods for treating pulp and paper mill effluent. In the present study, for the treatment of from pulp and paper industry, nine efficient fungal strains including Phanerochaete chrysosporium, dedicated for the selective degradation of lignin, have been isolated. Enzyme activities (Fpase, xylanases, lignin peroxidases and carboxy methyl cellulase) required for the degradation of lignocellulosic waste, protein and reducing sugar content were determined. Among all the strains, F3 (Paecilomyces sp.) strains showed highest activity of lignin peroxidase (3.3 IUml-1), Fpase (1.2 IUml-1), xylanase (0.85 IUml-1), CMcase (0.49 IUml-1), protein (2.8 mgml-1), and sugar content (2.1 mgml-1) at 120 h incubation period. Enzyme extracts of these fungal isolates were applied for the treatment of pulp and paper mill effluent. Data indicated that among all the strains, Paecilomyces sp. (F3) showed highest removal of colour (80 per cent) and other pollution parameters (73 per cent lignin, 78 per cent COD and 76 per cent AOX) in pulp and paper mill effluent, on day 3 at 3.3 international unit per ml concentration of crude enzymes.